Intensification of the development of wells at the Zahidnohrestyshchensky field - M. A. Myslyuk; V. P. Kravets (Мінеральні ресурси України)
Well completion technologies at the final stage of development of the Zahidnohrestyshchensky gas condensate field are described, the feature of which is hydraulic fracturing of productive layers before development. Information on the geological section and formation pressures, well designs, technologies for opening productive formations is provided. The concept of well completion technologies aimed at achieving high drilling rates, preventing complications and contamination of productive horizons is proposed. The model for choosing the optimal formulations of technological fluids for the opening of productive reservoirs and the development of wells has been formalized, which is reduced to substantiation with the help of expert procedures of the criterion of optimality and the construction of a system of restrictions on the concentration of reagents. The expediency of applying additive criteria of optimality, which take into account the filtration index of HTHP (High Temperature High Pressure), the interphase tension at the interface between the process fluid filtrate and the condensate, and rheological properties, was noted. Taking into account world and domestic experience, the requirements for scenarios of preparatory work and typical designs of fracturing technology operations with a content of 15 and 45 tonns of proppant are given. The industrial material of well development using hydraulic fracturing at the Zahidnohrestyshchensky field, as well as some research results using the Baker Hughes Mayer Mfrac software, are systematized. The results of the analysis of industrial data on the development of wells from hydraulic fracturing at the Zahidnohrestyshchensky field are given. A statistically significant correlation was established between the productivity index after fracturing at the beginning and after 6 months of operation and the volume of the working mixture and proppant mass, as well as its absence for the maximum pressure at the wellhead. Statistical hypotheses about the equality of correlation coefficients for the analyzed parameters after fracturing and 6 months of well operation were confirmed.